Integrating Islamic Values and Science for Millennial Students’ Learning on Using Seamless Mobile Media - Fahyuni, E. F.; Wasis, W.; Bandono, A.; Arifin, M. B. U. B. (Jurnal Pendidikan IPA Indonesia, 2020)
This research aims to facilitate and assist student learning in finding, gathering and analyzing what is needed to develop spiritual potential, self-control, personality, intelligence, noble character, by using seamless mobile media to get the required help in his life. Integration with guided inquiry learning the values of Islam and science in the phenomenon of natural at millennial students utilize information technology of learning resources available environment. The concurrent triangulation strategy is done by collecting quantitative and qualitative data concurrently, then comparing the two databases related to the presence or absence of convergence, differences, or combination. Based on this multivariate statistic analysis, there are differences in learning outcomes between millennial students who use seamless mobile media and non-seamless mobile media. Efforts to integrate Islamic values and science are realized learning outcomes that are; 1) wisdom of greatness, 2) usefulness in life, 3) artificial projects, 4) written reports, 5) responsibilities, 6) accuracy, 7) curiosity. The results of learning patterns that integrate Islamic values and science using seamless mobile media increase students’ skills, abilities, and knowledge. The millennial students can complete artificial projects and report very well their meaningful learning activities to have gratitude to all who made God’s creation on Earth. Efforts to integrate Islamic values and science essential to develop knowledge and ethical character. In Islam, every human being born in a sacred environment, and education becomes a deciding factor in the quality of a child’s religion by providing learning of meaning to improve the quality of millennial students.